Therapeutic Potential of Secretome Hypoxia Mesenchymal Stem Cells: Downregulation of TNF-α and HIF-2α in Metabolic Syndrome-Induced Inflammation in Wistar Rats - Dewi, Alisia Martha; Trisnasi, Setyo; Putra, Agung; Chodijah , Chodijah; Sarosa, Hadi; Mulyani, Sri Priyantini; Amalina, Nur Dina; Ibrahim, Sugeng (Universitas Negeri Semarang, 2024)
Background: Metabolic syndrome (MetS) has become a global health challenge with several associated issues, such as obesity, insulin resistance, dyslipidemia, and hypertension. Important proteins such as Tumor Necrosis Factor-alpha (TNF-α) and Hypoxia Inducible Factor-2 alpha (HIF-2α) regulate the inflammatory process by inducing the expression of pro-inflammatory proteins. Secretome Hypoxia Mesenchymal Stem Cells (SH-MSCs) are immunomodulatory, anti-inflammatory, and angiogenic stimulators, which can regulate various inflammatory diseases, including MetS. Objective: This study aims to determine the effect of administering SH-MSCSs on the expression of the TNF-α and Hypoxia Inducible Factor (HIF)-2α genes in the male Wistar rat model with Metabolic Syndrome. Method: This research is an experimental study with a Post-test Only Control Group Design, using a total of 24 male Wistar rats divided into four groups: T1 (Healthy control), T2 (MetS + NaCl), T3 (MetS + administration of SH-MSCs dose 150 uL), and T4 (MetS + administration of SH-MSCs dose 300 uL). SH-MSCSs were administered intraperitoneally four times over 14 days. Adipose tissue TNF-α and HIF-2α gene expression were measured on day 15 using qRT-PCR. Results: TNF-α and HIF-2α gene expression was significantly lower in T3 and T4, compared with the MetS control group (T2). Conclusion: Administration of SH-MSCs was able to reduce the expression of the Tumor Necrosis Factor (TNF-α) and Hypoxia Inducible Factor (HIF)-2α genes in fatty tissue in the male Wistar rat model with Metabolic Syndrome.